RELEVANSI NILAI : INFORMASI LABA, ARUS KAS, NILAI BUKU, GOODWILL DAN UKURAN PERUSAHAAN YANG MEMBENTUK KEPUTUSAN EKONOMI INVESTOR - LUH PUTU WIDA P, NI (Jurnal Akuntansi AKUNESA, 2014)
Value relevance of accounting information is the ability of accounting information to explain the company's market value. Relevance of a financial statement can be seen from how much influence the financial statements on capital market activity. An information have content if the market will react quickly and it can be observed in changes in market prices. The purpose of this study is test whether there is a positive effect of earnings, cash flow, book value, goodwill, and size of the company to the stock price. Data used is gross profit, total sales, operating cash flow, total equity, goodwill, total assets, number of shares outstanding and the closing price on March from financial statement and ICMD period 2010-2013. The samples in this study were 11 companies listed on the Indonesian Stock Exchange. The research method used is quantitative. The results show that based on the simultant test between gross profit, operating cash flow, book value, goodwill and total assets to the stock price is significant. The partial test show gross profit and operating cash to stock price is significant. Book value of equity, goodwill and total assets to srock price is insignificant based on the partial test.   Keywords: value relevance, price stock, gross profit, operating cash flow, book value of equity